2006
DOI: 10.1128/jvi.80.1.360-371.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role for nsP2 Proteins in the Cessation of Alphavirus Minus-Strand Synthesis by Host Cells

Abstract: In order to establish nonlytic persistent infections (PI) of BHK cells, replicons derived from Sindbis (SIN) and Semliki Forest (SFV) viruses have mutations in nsP2. Five different nsP2 PI replicons were compared to wild-type (wt) SIN, SFV, and wt nsPs SIN replicons. Replicon PI BHK21 cells had viral RNA synthesis rates that were less than 5% of those of the wt virus and ϳ10% or less of those of SIN wt replicon-infected cells, and, in contrast to wt virus and replicons containing wt nsP2, all showed a phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 61 publications
(65 reference statements)
6
51
0
Order By: Relevance
“…It has been found that nsP2 expresses functions that are involved in the regulation of the host response to infection (6,9,11,26,32). One of its regulatory activities might be an overall cessation of negative-strand synthesis that is observed at 4 to 8 h p.i., depending on the cell type (33,35).…”
Section: Sinv Variants With Mutated Cleavage Cites In Ns Polyproteinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that nsP2 expresses functions that are involved in the regulation of the host response to infection (6,9,11,26,32). One of its regulatory activities might be an overall cessation of negative-strand synthesis that is observed at 4 to 8 h p.i., depending on the cell type (33,35).…”
Section: Sinv Variants With Mutated Cleavage Cites In Ns Polyproteinmentioning
confidence: 99%
“…Moreover, like the nsP2 proteins of other alphaviruses (25), SINV nsP2 is coisolated with ribosomes from infected cells (1), but its functional role in these complexes is unknown. Specific amino acid substitutions in SINV and SFV nsP2 strongly affected the ability of the protein to modify the intracellular environment (6,26,32); the mutations altering the carboxy-terminal fragment of nsP2 made viruses attenuated in vivo and incapable of inhibiting host cell transcription and/or translation (9,13,14). Thus, accumulated data suggest that the processing of SINV and SFV nsP precursors plays a role not only in the temporal regulation of negative-and positive-strand viral RNA syntheses by the RC but also in the modification of the cellular response to infection.…”
mentioning
confidence: 99%
“…The four nonstructural proteins produced, nsP1 to nsP4, are involved in RNA replication and modification and in proteolytic cleavage. A leaky opal stop codon near the 3= end of the nsP3 gene is present in the genomes of most but not all alphaviruses (42,51), such that two products, P123 and P1234, are produced during translation (63,71). The second polyprotein encodes the structural proteins, including the capsid protein, two major envelope proteins (E2 and E1), and two smaller structural proteins not usually found in virions (23,71).…”
mentioning
confidence: 99%
“…This is useful in eliminating a target cell or in triggering an immune response (11,18). The use of noncytotoxic SFV vectors would lead to long-lasting but weak expression (39). Alternatively, cells that do not support SFV replication exist, and provided that they allow a high retroviral budding, the use of a Pol II-dependent expression system for a ⌿ MLV SFV vector (5,18,34) should promote the efficient formation of retrovirus particles containing the full-length vector.…”
Section: Fig 3 (A and B)mentioning
confidence: 99%